An attenuated coxsackievirus B5 mutant carrying VP1-N157K retains oncolytic potency against non-small cell lung cancer - Lifang Song; Bopei Cui; Qiushuang Gao; Chaoying Hu; Qian wang; Jialu Zhang; Yajing Li; Guanxing Liu; Yulong Fu; Ying Wang; Kelei Li; Xiaotian Hao; et al. (Molecular Therapy: Oncology, 2025)
Oncolytic virus therapy is a rapidly developing cancer treatment method. The development of oncolytic viruses often involves genetic modifications, such as increased expression of foreign proteins for enhancing the antitumor capabilities and knocking out of virulence loci for improving the safety. The wild-type coxsackievirus B5 (CV-B5/F) exhibits potent antitumor activity against non-small cell lung cancer. However, CV-B5 poses pathogenic risks to infants and young children, warranting further virulence attenuation to develop a safe strain. No attenuating locus has been reported for CV-B5. In this study, we attenuated the original strain CV-B5/F by low-temperature passage for 30 generations and identified the virulence locus N157K in the structural protein VP1 using reverse genetics analysis. The attenuated strain carrying VP1-N157K retained the antitumor capabilities as the original strain. In addition, an exploration of the potential attenuation mechanisms revealed that the VP1-N157K mutation site weakened the replication ability of CV-B5. In summary, we identified a key virulence locus of CV-B5 and constructed an attenuated strain, which retains the oncolytic activity of the wild-type strain against non-small cell lung cancer with increased safety.